Sleep quality and its relationship with night eating syndrome, the risk of diabetes, and nutritional status among university students - Akdevelioğlu, Yasemin; Şahin, Teslime Özge; Yesildemir, Ozge (Progress in Nutrition, 2020)
Changes in sleep quality increase the risk of diabetes and obesity by affecting nutrition. This study was conducted to find the correlation between sleep quality and night eating syndrome in addition to obesity predisposition and the risk of diabetes. 550 university students including 330 women and 220 men between the ages of 17-42 years participated in the study. A face to face questionnaire was conducted in order to collect information about their personal characteristics, nutritional habits, and physical activities. Their anthropometric measurements were taken and food consumption in the last 24 hours were recorded. The Night Eating Syndrome Questionnaire, the Pittsburg Sleep Quality Index, and the Finnish Diabetes Risk Score were conducted on the participants. 40% of the students were found to have good sleep quality, while 60% were found to have poor sleep quality. The median values of night eating syndrome, the risk of diabetes, and the sleep quality scores of participants with good sleep quality were significantly lower than that of the participants with poor sleep quality. Also, a positive correlation was found between the sleep quality score along with the night eating and diabetes risk scores. Moreover, night eating syndrome and sleep duration were positively correlated with waist circumference and waist/height ratio which are indicators of obesity. As a result, the study found that poor sleep quality increased night eating syndrome, obesity predisposition, and the risk of diabetes, a metabolic disease. University students may be recommended to improve their sleep quality in order to prevent the above-mentioned metabolic diseases.